Profile of outer membrane proteins of carbapenem-resistant Gram-negative bacilli in Ghana - Francis S. Codjoe; Fleischer C. N. Kotey; Eric S. Donkor (BMC Research Notes)
Abstract Objective Carbapenem resistance is a major global health threat, but insights on its molecular determinants are scanty in sub-Saharan Africa, the predominant global antimicrobial resistance hotspot. This study aimed to profile outer membrane proteins (OMPs) of 111 carbapenem-resistant Gram-negative bacteria recovered from a broad spectrum of clinical specimens from Ghana. Results The OMPs of Pseudomonas aeruginosa produced decreased amounts of OprD or the porin was completely lost, except in 5.9% (n = 3) of the isolates which had high-level porins. For Acinetobacter baumannii, 96.8% (n = 30) expressed loss of OprF. One carbapenemase non-PCR-positive isolate with high-level porin expression was observed. In A. baumannii, the major and significant band on SDS-PAGE was ~ 35 kDa. There were substantial numbers of unrelated porin expression among the isolates. Particularly, OmpC/F or OmpK35/37 expression was deficient. Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) analysis for Escherichia coli, Klebsiella aerogenes, Klebsiella pneumoniae, and other Enterobacterales had OmpC and OmpF absent or markedly reduced compared to the control strains. Overall, porin loss was a major mechanism underlying carbapenem resistance among the isolates, suggesting that in carbapenem-resistant organisms that seem to lack known carbapenem resistance genes, porin loss may be the underlying carbapenem resistance mechanism.